Formulation of Islamic Religious Education Teacher Competencies to Foster Digital Morals of Students in the Social Media Era - Masfufah Masfufah; Nikmatus Sholicha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rapid development of social media has created a disjunction between the moral values taught in Islamic Religious Education (PAI) and students' complex and often problematic digital behavior. PAI teachers are at the forefront of facing the challenge of guiding students to navigate ethically in cyberspace, yet their functions and competencies have not been adequately defined to meet today's demands. This study aims to critically analyze the conceptualization and implementation of PAI teachers' pedagogical functions in shaping students' digital morals and ethics, identify the fundamental problems they face, and formulate a new, relevant competency model. Using a qualitative approach with a literature review method analyzed through thematic synthesis, this study integrates findings from various credible scientific sources. The analysis shows that PAI teachers are in the process of reconceptualizing their function, shifting from normative instructors to facilitators and moral role models in the digital world. However, its implementation is hampered by fundamental problems including the digital literacy gap, psychological burden, and a lack of systematic institutional support. In response to these challenges, this study formulates a new competency model for Islamic Religious Education teachers consisting of six main pillars: (1) critical digital pedagogy, (2) proactive moral guidance, (3) ecosystemic collaboration, (4) contextual learning design, (5) personal resilience and adaptability, and (6) education policy advocacy. This model offers an integrated framework to equip Islamic Religious Education teachers with the capabilities needed to effectively shape a digitally competent, ethically mature, and morally upright young generation. This study has implications for the need for reform in teacher education curricula and professional development policies for religious educators in the digital era.